Adobe Photoshop Elements 7. (Classroom in a book., 2008)
The fastest, easiest, most comprehensive way to learn Adobe Photoshop Elements Classroom in a Book®, the best-selling series of hands-on software training workbooks, helps you learn the features of Adobe software quickly and easily. Classroom in a Book off ers what no other book or training program does--an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts. Adobe Photoshop Elements 7 Classroom in a Book contains 11 lessons. The book covers the basics of learning Adobe Photoshop Elements and provides countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. TABLE OF CONTENTS: GETTING STARTED 1 A QUICK TOUR OF PHOTOSHOP ELEMENTS 2 BASIC ORGANIZING 3 ADVANCED ORGANIZING 4 CREATING PROJECTS 5 PRINTING, SHARING, AND EXPORTING 6 ADJUSTING COLOR IN IMAGES 7 FIXING EXPOSURE PROBLEMS 8 REPAIRING AND RETOUCHING IMAGES 9 WORKING WITH TEXT 10 COMBINING MULTIPLE IMAGES 11 ADVANCED EDITING TECHNIQUES "The Classroom in a Book series is by far the best training material on the market. Everything you need to master the software is included: clear explanations of each lesson, step-by-step instructions, and the project files for the students." Barbara Binder Adobe Certified Instructor Rocky Mountain Training